УСТАВНИ ОКВИРИ ПРОЦЕСА ДЕЦЕНТРАЛИЗАЦИЈЕ И РЕФОРМЕ УПРАВЉАЊА ДРЖАВОМ НА ПРИМЕРИМА СРБИЈЕ И ХРВАТСКЕ - Čiplić, Svetozar; Martinović, Aleksandar L; Rajić, Nataša N (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Abstract:THE WORK IS DEVOTED TO THE COMPARATIVE ANALIZE OF THE PROCESSES OF THE DECENTRALIZATION REORGANIZATION AND REFORM OF THE PUBLIC ADMINISTRATION AT THE LEVEL OF THE HORIZONTAL GOVERNANCE ORGANIZATION IN SERBIA AN CROATIA. AT THE FRST PART OF THE WORK AHE AUTHORS ANALIZE THE DECENTRALIZATION AND DEVOLUTION AS WELLAS THEIRDEMARCATION IN THE SENSE OF THEIR RELATED BUT NOT SIMILAR MEANINGS. THE SECOND PART IS DEVOTED TO THE HISTORICAL EXPERIENCES AND GENESIS FOUNDATIONS OF THE COMMON STATE WHERE SERBIA AND CROATIA WHERE SERBIA AND CROATIA WERW JOINED. THE PARTICULAR HISTORICAL DEVELOPMENTS OF SERBIA AND CROATIA INFLUENCED THE PRESENT ATTITUDE OF THEIR POLITICAL ELITES TOWARD DECENTRALIZATION. THE THIRD, FINAL PART / CONCLUSION, IS DEDICATED TO A COMPARATIVE ANALYSES OF THE CONSTITUCIONAL SOLUTIONS IN SERBIA AND CROATIA WHICH ARE RELATED TO THE VERTICAL ORGANIZATION. Key word: DECENTRALIZATION, GOVERNANCE REFORM, GOVERNANCE DISPERZIONM LIMITATION OF THE GOVERNANCE, DEVOLUTION.